2008
DOI: 10.1152/ajplung.00186.2007
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of deposition pattern and pulmonary response as a result of improved dispersion of aspirated single-walled carbon nanotubes in a mouse model

Abstract: Nanoparticles have a fundamental dimension of <100 nm. However, on suspension in media, agglomerates of nanoparticles are the more common structure. This is particularly evident in prior intratracheal instillation or aspiration studies of single-walled carbon nanotubes (SWCNT), in which granulomatous lesions encased by epithelioid macrophages were produced by large agglomerates. In this study, we tested the hypothesis of whether exposure to more dispersed SWCNT structures would alter pulmonary distribution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
322
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(347 citation statements)
references
References 26 publications
20
322
1
1
Order By: Relevance
“…Secondary antibodies were Rhodamine Red goat anti-rabbit IgG and Alexa 488 goat anti-mouse IgG (Invitrogen, Carlsbad, CA). Small aggregates of SWCNT (carbon nanoropes) appeared as black structures in differential interference contrast (DIC) imaging due to absorbance of light [39][40][41]. The morphology of the mitotic spindle and centrosome, and the relationship with carbon nanoropes, was analyzed in the BEAS-2B cells using a laser scanning confocal microscope (LSM 510, Carl Zeiss MicroImaging Inc., Thornwood, NY) as previously described [25].…”
Section: Mitotic Spindle and Centrosome Morphology Analysismentioning
confidence: 99%
“…Secondary antibodies were Rhodamine Red goat anti-rabbit IgG and Alexa 488 goat anti-mouse IgG (Invitrogen, Carlsbad, CA). Small aggregates of SWCNT (carbon nanoropes) appeared as black structures in differential interference contrast (DIC) imaging due to absorbance of light [39][40][41]. The morphology of the mitotic spindle and centrosome, and the relationship with carbon nanoropes, was analyzed in the BEAS-2B cells using a laser scanning confocal microscope (LSM 510, Carl Zeiss MicroImaging Inc., Thornwood, NY) as previously described [25].…”
Section: Mitotic Spindle and Centrosome Morphology Analysismentioning
confidence: 99%
“…Aspiration of a well-dispersed suspension of SWCNTs resulted in a less severe granulomatous response and a 4-fold greater interstitial fibrotic response than a poorly dispersed SWCNT suspension. 15 Furthermore, aspiration of gold-labeled SWCNTs demonstrated that agglomerates induced granulomatous lesions in the terminal bronchioles and proximal alveoli, while more dispersed SWCNT structures deposited in the distal lung, rapidly entered the alveolar interstitium, and caused progressive fibrosis. 15 Aspiration of purified MWCNTs in mice caused a similar spectrum of pulmonary responses as SWCNTs, that is, rapid but transient damage and inflammation, granulomatous lesions, and interstitial fibrosis.…”
Section: A Pulmonary Responsesmentioning
confidence: 99%
“…15 Furthermore, aspiration of gold-labeled SWCNTs demonstrated that agglomerates induced granulomatous lesions in the terminal bronchioles and proximal alveoli, while more dispersed SWCNT structures deposited in the distal lung, rapidly entered the alveolar interstitium, and caused progressive fibrosis. 15 Aspiration of purified MWCNTs in mice caused a similar spectrum of pulmonary responses as SWCNTs, that is, rapid but transient damage and inflammation, granulomatous lesions, and interstitial fibrosis. 16 Short-term inhalation (4 days) of MWCNTs induced pulmonary responses in mice similar to those reported after aspiration.…”
Section: A Pulmonary Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the results of the characterization of the MWCNT samples, the authors noted that the lengths of individual MWCNTs were greatly altered by grounding, from 5.9 µm to 0.7 µm, but the other main characteristics such as tube diameter and specific surface area were not changed by the operation. In addition, in a study by Mercer et al 61) , mice were subjected to pharyngeal aspiration exposure to dispersed SWCNTs (particle size, 0.69 µm) and non-dispersed SWCNTs (particle size, 1.52 µm), and it was reported that thickening of the alveolar wall was found only in the groups exposed to dispersed SWCNTs. The authors considered that the dispersed SWCNTs would more easily penetrate the interstitium.…”
Section: Carbon Nanotubesmentioning
confidence: 99%